Ambulatory Single-level Posterior Cervical Foraminotomy for Cervical Radiculopathy: A Propensity-matched Analysis of Complication Rates. Issue 2 (March 2022) - Bovonratwet, Patawut; Retzky, Julia S.; Chen, Aaron Z.; Ondeck, Nathaniel T.; Samuel, Andre M.; Qureshi, Sheeraz A.; Grauer, Jonathan N.; Albert, Todd J.
Abstract : Study Design: Retrospective cohort comparison study. Objective: The aim was to compare perioperative complications and 30-day readmission between ambulatory and inpatient posterior cervical foraminotomy (PCF) in the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database. Summary of Background Data: Single-level PCF for cervical radiculopathy is increasingly being performed as an ambulatory procedure. Despite this increase, there is a lack of published literature documenting the safety of ambulatory PCF. Materials and Methods: Patients who underwent PCF (through laminotomy or laminectomy) were identified in the 2005–2018 NSQIP database. Ambulatory procedures were defined as cases that had hospital length of stay=0 days. Inpatient procedures were defined as cases that had length of stay=1–4 days. Patient characteristics, comorbidities, and procedural variables (laminotomy or laminectomy performed) were compared between the 2 cohorts. Propensity score matched comparisons were then performed for postoperative complications and 30-day readmissions between the 2 groups. Results: In total, 795 ambulatory and 1789 inpatient single-level PCF cases were identified. After matching, there were 795 ambulatory and 795 inpatient cases. Statistical analysis after propensity score matching revealed no significant difference in individual complications including 30-day readmission, thromboembolic events, wound complications, and reoperation, or aggregated complications between ambulatory versus matched inpatient procedures. Overall 30-day readmissions after ambulatory single-level PCF were noted for 2.46% of the study population, and the most common reasons were surgical site infections (46%) and pain control (15%). Conclusions: The perioperative outcomes assessed in this study support the conclusion that single-level PCF for cervical radiculopathy can be performed for correctly selected patients in the ambulatory setting without increased rates of 30-day perioperative complications or readmissions compared with inpatient procedures. Level of Evidence: Level III.